Molecular Mechanics and Semi-empirical Analyses of the Interaction between Nickel(II) and L-histidine and L-arginine in Solution in Water - Huq, Fazlul; C.R. Peter, Marie (Asian Journal of Chemistry, 2010)
The interaction between nickel(II) and the amino acids (viz., L-histidine and L-arginine) in solution in water has been investigated by UV-visible spectrophotometry using the technique of continuous variation and molecular modelling. The absorbance values at λmax were plotted against concentrations of reactants. The maxima in the absorbance vs concentration graphs gave the ratios at which the metal ion and amino acids combined. Nickel(II) is found to form predominantly 1:3 complex with both L-histidine and L-arginine. As expected, the d-d absorption bands due to nickel(II) have been found to show a shift to shorter wavelengths when complexed with L-histidine and L-arginine. The proposed structures of the complexes have been optimized and their electronic spectra generated based on molecular mechanics and semi-empirical calculations. Comparison of the observed and predicted electronic spectra suggested the most likely structures present in solution.